Kinematics of the jump floater serve in elite female volleyball players - Horiuchi, G.; Toyoshima, R.; Suzuki, Y.; Sakurai, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of this study was to clarify the kinematics of the jump floater serve in volleyball to provide basic data for research. The jump floater serve motions of 9 female volleyball players (body height: 174.4±6.2 cm, body weight: 67.7±6.1 kg, age: 23.6±4.6 yr, career: 14.4±5.1 yr) were recorded using a motion capture system with 10 cameras (500 Hz). The three-dimensional coordinates of retro-reflective markers on the volleyball were also collected using a motion capture system. The primary variables examined were the hand velocity of the swing arm at impact, the velocity and angular velocity of the volleyball after impact, the joint angles of the swing arm and torso, and the segment angle of the lower torso during the jump floater serve. The main results were as follows. 1. The speed of the volleyball was about 14 m/s, and the spin of the volleyball was about 1 rps. 2. No significant correlation was found between the number of volleyball rotations around each axis and the impact parameters of the swing hand. 3. The maximal right rotation angle of the torso joint in the jump floater serve was smaller than that of the spike motion. 4. The abduction angle of the shoulder joint at ball impact in the jump floater serve was similar to that of a spike motion. 5. From the end of take back to the middle of the serve motion, the standard deviation in the abduction angle of the shoulder joint was notably large. 6. The maximal external rotation of the shoulder joint was smaller in comparison with a baseball pitch or a tennis serve. 7. The extension angle of the elbow joint at impact was smaller in comparison with the volleyball spike motion.